Original paperEvaluation of neuropathic pain occurring after high- dose-rate interstitial brachytherapy of oral tongue - Simha, Vijai; Sharma, Suresh C.; Kapoor, Rakesh; Ahuja, Chirag K.; Oinam, Arun S.; Ghoshal, Sushmita (Journal of Contemporary Brachytherapy, 2015)
Purpose: To recognize neuropathic pain as a complication of high-dose-rate (HDR) interstitial brachytherapy of oral tongue and to evaluate the possible causes of neuropathy. Material and methods: Twenty one patients who underwent interstitial brachytherapy for early cancer of oral tongue were evaluated. The patients either underwent primary brachytherapy (42-48 Gy at 3-4 Gy/fraction) or a boost (18-24 Gy at 3 Gy/fraction) after external radiation to 40 Gy. Lingual nerve was the nerve concerned and the sublingual space (SLS) was contoured as its surrogate. Dosimetric parameters were correlated with onset of pain. Results: Ten patients out of 21 (47.61%) developed painful neuropathy. Five patients of six (5/6) who underwent primary brachytherapy developed neuropathy. Five out of 15 (5/15) patients who underwent brachytherapy as a boost developed neuropathy. The patients who underwent primary brachytherapy were ten times more likely to develop neuropathy. Among the patients receiving boost treatment, the equivalent dose at 2 Gy/fraction (EQD2) to 2 cc of SLS was higher (39.25 Gy) in the patients who developed pain compared to those without pain (10.29 Gy). Conclusions : This is the first report to recognize neuropathic pain as a complication of HDR brachytherapy of oral tongue. Patients undergoing primary brachytherapy were more likely to develop pain. Among other factors like dose to SLS, number of catheters, size of the primary tumor, and the dose rate, only dose to 2 cc of the SLS correlated with onset of pain. The SLS (containing the lingual nerve) may be considered an organ at risk to prevent the occurrence of this complication.